2014
DOI: 10.1590/1982-43272457201409
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies Among Brazilian Pregnant Women Living With HIV

Abstract: Pregnant women living with HIV (PWLH) face tremendous challenges in order to prevent their babies’ infection. Coping is a potential buffer against negative outcomes from these challenges. This study aims to describe coping strategies of PWLH. This cross-sectional survey involved 77 PWLH from a public health care center in Brazil. Coping was measured for three types of strategies: Problem-focused, Emotion-focused, and Relationship support. Multivariate analyses identified some coping predictors. Being employed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Our study findings showed that some participants who had limited support from their partners became self-reliant to provide for themselves and their child. This finding is consistent with previous work showing that economic stability helps women with HIV to cope positively and overcome HIV-related stressors [ 54 , 55 ]. Although women are able to cope and are important actors, they should not be saddled with all the responsibility.…”
Section: Discussionsupporting
confidence: 93%
“…Our study findings showed that some participants who had limited support from their partners became self-reliant to provide for themselves and their child. This finding is consistent with previous work showing that economic stability helps women with HIV to cope positively and overcome HIV-related stressors [ 54 , 55 ]. Although women are able to cope and are important actors, they should not be saddled with all the responsibility.…”
Section: Discussionsupporting
confidence: 93%
“…This resulted in a reduction of access to the material and symbolic goods that could have enhanced their education and career prospects, increased their ability to exercise sexual and reproductive rights and autonomy in affective and sexual relationships, and expanded their social support network; elements which improve coping with the stigma attached to HIV/AIDS, understood as getting on with life and making plans regardless of the disease 14,15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative study. P = 841 people with HIV and 89 coordinators and professionals from HIV programs Article 23 (35)…”
Section: United Kingdom and Irelandmentioning
confidence: 99%
“…The study pointed out that health professionals face a dilemma due to a general understanding that gestation in women with HIV is "itself" a "risk pregnancy" for both the mother and the baby, and for the partner who, in theory, is exposed to the infection, once the pregnancy is confirmed, it is made explicit the practice of unprotected sex (27) . A quantitative study in Porto Alegre with 77 HIV-positive pregnant women showed that the Brazilian strategies remain focused on the prevention of virus VT (21,35) . The risk of VT is used by health professionals both to discourage an intention to become pregnant and to guide the prophylaxis of VT (21) .…”
Section: Care Provided and Not Provided By Health Professionals To Womentioning
confidence: 99%